Simultaneous improvement of mechanical strength, ductility and corrosion resistance of stir cast Al7075-2% SiC micro- and nanocomposites by friction stir processing. (December 2017) - Kumar, Atul; Pal, Kaushik; Mula, Suhrit
Graphical abstract: Highlights: Stir casting followed by FSP is a promising route to develop Al based nanocomposite. Distribution of SiC nanoparticle is improved with matrix grain refinement after FSP. Strength and ductility of the composites are improved simultaneously after FSP. Corrosion potential of the composites are shifted towards noble direction after FSP. Abstract: Present work investigates the mechanisms of simultaneous improvement of tensile properties, wear properties and corrosion resistance of stir cast Al7075–2 wt.% SiC micro- and nanocomposites through microstructural refinement by friction stir processing (FSP). Optical, scanning and transmission electron microscopy were used to investigate the microstructural evolution. After the FSP, the nanoparticles reinforced composite showed better mechanical properties than that of the microparticles reinforced composite. Tensile strength ( >3 times) and wear resistance were found to increase significantly with simultaneous enhancement of the ductility (10 times). The improvement is ascribed to the grain size reduction, distribution of SiC nanoparticles uniformly within the matrix, increase particle-matrix interface characteristics and elimination of casting defects such as porosity after the FSP. The corrosion potentials of the as-cast composites were found to shift towards noble direction after the FSP. Enhancement of corrosion resistance after the FSP is attributed to the decrease in the heterogeneity on the surface and uniform dispersion of the reinforced particles, which reduced the effective active surface area exposed to the corrosive solution. All such beneficial effects were found to be superior for the nanoparticles reinforced composite due to the improved particle/matrix interface characteristics and dispersion strengthening.